承認與創造——對〈承認理論的創造論回歸〉一文的評論性回應: Recognition and Creation: A Critical Review - HONG, Liang (International Journal of Chinese & Comparative Philosophy of Medicine, 2022)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 在〈承認理論的創造論回歸一一一項關於人倫構成的哲學研究〉一文中，唐文明(以下簡稱作者)圍繞倫理共同體的超越性奠基這一核心問題，從分析黑格爾與霍耐特的承認理論之得失出發，引入阿倫特對奥古斯丁記憶理論的闡發及其提出的“誕生性”概念，力圖在古代儒學語境中釐清天人之倫的垂直向度對於人人之倫的水準向度所具有的前提性意義。(撮要取自內文首段) Professor Tang’s essay successfully presents the theoretical connection between the theory of recognition and the doctrine of creation in the Christian and Confucian traditions. The following critical review consists of four parts: (1) an evaluation of Tang’s method of intellectual history, (2) a criticism of Tang’s reading of Descartes’ third meditation, (3) an analysis of Arendt’s concept of natality, and (4) a discussion of the importance of gender equality in the Confucian moral theory of society.